2017
DOI: 10.1007/978-1-4939-7201-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Disease-Related Protein Assemblies for Single Particle Electron Microscopy

Abstract: Electron microscopy (EM) is a rapidly growing area of structural biology that permits us to decode biological assemblies at the nanoscale. To examine biological materials for single particle EM analysis, purified assemblies must be obtained using biochemical separation techniques. Here we describe effective methodologies for isolating histidine (his)-tagged protein assemblies from the nucleus of disease-relevant cell lines. We further demonstrate how Isolated assemblies are visualized using single particle EM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We and others have shown that mouse FPC-CTD is proteolytically cleaved through Notch-like processing ( Kaimori et al, 2007 ; Follit et al, 2010 ; Cameron Varano et al, 2017 ). The FPC-CTD traffics into the nucleus and binds to double stranded DNA as a member of a ring-structure protein complex ( Kaimori et al, 2007 ; Follit et al, 2010 ; Cameron Varano et al, 2017 ). However, it is not clear how FPC-CTD regulates gene expression, or which genes are regulated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have shown that mouse FPC-CTD is proteolytically cleaved through Notch-like processing ( Kaimori et al, 2007 ; Follit et al, 2010 ; Cameron Varano et al, 2017 ). The FPC-CTD traffics into the nucleus and binds to double stranded DNA as a member of a ring-structure protein complex ( Kaimori et al, 2007 ; Follit et al, 2010 ; Cameron Varano et al, 2017 ). However, it is not clear how FPC-CTD regulates gene expression, or which genes are regulated.…”
Section: Discussionmentioning
confidence: 94%
“…The mFPC-CTD, encoded by exons 65-67, undergoes Notch-like processing followed by regulated membrane-release and translocation to the nucleus ( Kaimori et al, 2007 ), which is facilitated by the 25-residue long nuclear localization signal (NLS) ( Hiesberger et al, 2006 ). Single particle electron microscopy analysis revealed that FPC-CTD forms a ring-like protein complex that binds to double stranded DNA, suggesting a role in gene expression regulation ( Cameron Varano et al, 2017 ). Yet, the function of FPC-CTD in the nucleus remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%